Association between short-term annoyance and several physiological parameters during different amounts of nocturnal aircraft noise exposure - Ohlenforst, B.A.; Miltenburg, M.P.G. van; Aalmoes, R.; Schreckenberg, D.; Ligthart, S. (ŁUKASIEWICZ RESEARCH NETWORK – INSTITUTE OF AVIATION, 2020)
Annoyance is the most prevalent community response to environmental noise. Observational and experimental lab studies have shown that exposure to environmental noise leads to annoyance, sleep disturbance, daytime sleepiness, increased heart rate and increased blood pressure. However, previous literature is preliminary based on controlled settings or experimental design, raising the question of the generalizability and applicability in daily life scenarios. This study aimed to investigate two main research questions. First, what is the relationship between short-term annoyance and different amounts of nocturnal aircraft noise exposure in daily life? Second, what is the relationship between physiological parameters, including heart rate, number of awakenings, sleep efficiency, sleep duration and different amounts of nocturnal aircraft noise exposure in daily life? This study also aimed to explore the suitability of non-invasive commercially available activity trackers to measure physiological metrics in a scientific way. During this field study, participants were wearing Fitbit Charge 3 activity trackers recording heart rate and different sleep-derived metrics (e.g. deep sleep duration, sleep efficiency and awakenings). The used activity trackers were readily available, non-intrusive, relatively cheap and easy to use by the participants. Simultaneously, a logbook was used by the participants to track the subjective perception and situational context of air traffic noise exposure. The noise levels corresponding to the exposure of air traffic of each participant were calculated based on the location of the participant and the corresponding radar track using an aircraft noise monitoring system.